CGIAR’s SAPLING Initiative targets Uganda’s pig and cattle sectors to expand benefits for farmers - International Livestock Research Institute (CGIAR System Organization, 2022)
Co-creation, with stakeholders, of the SAPLING vision and theory of change for the pig, dairy cattle and beef cattle value chains in Uganda